2012
DOI: 10.1093/jxb/ers161
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide-activated calcium/calmodulin-dependent protein kinase regulates the abscisic acid-induced antioxidant defence in maize

Abstract: Nitric oxide (NO), hydrogen peroxide (H2O2), and calcium (Ca2+)/calmodulin (CaM) are all required for abscisic acid (ABA)-induced antioxidant defence. Ca2+/CaM-dependent protein kinase (CCaMK) is a strong candidate for the decoder of Ca2+ signals. However, whether CCaMK is involved in ABA-induced antioxidant defence is unknown. The results of the present study show that exogenous and endogenous ABA induced increases in the activity of ZmCCaMK and the expression of ZmCCaMK in leaves of maize. Subcellular locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 61 publications
1
64
1
2
Order By: Relevance
“…This finding strengthens the hypothesis that nitrite rather than nitrate had a positive effect in hypoxic tissue (Horchani et al 2011). Since nitrite was effective at very low concentration, its role was suggested not to be restricted to the regeneration of NAD(P) + , but rather linked to a regulatory mechanism related to NO emission (Talwar et al 2012;Ma et al 2012;Zhang et al 2007;Libourel et al 2006).…”
Section: Nitrite Reduction and Nitric Oxide Productionsupporting
confidence: 82%
“…This finding strengthens the hypothesis that nitrite rather than nitrate had a positive effect in hypoxic tissue (Horchani et al 2011). Since nitrite was effective at very low concentration, its role was suggested not to be restricted to the regeneration of NAD(P) + , but rather linked to a regulatory mechanism related to NO emission (Talwar et al 2012;Ma et al 2012;Zhang et al 2007;Libourel et al 2006).…”
Section: Nitrite Reduction and Nitric Oxide Productionsupporting
confidence: 82%
“…Tobacco (Nicotiana tabacum) CCaMK was indicated to play a role in controlling the development of anther (Poovaiah et al, 1999), and pea (Pisum sativum) CCaMK was up-regulated in roots in response to low temperature and salt treatment (Pandey et al, 2002). Recent results showed that CCaMK from maize (Zea mays; ZmCCaMK) and rice (OsCCaMK) both play important roles in abscisic acid-induced antioxidant protection (Ma et al, 2012;Shi et al, 2012). Together, these results suggest that CCaMK acts as a multifunctional regulatory protein in plants.…”
Section: +mentioning
confidence: 99%
“…It was also found that OsDMI3 functions upstream to OsMPK1 in regulating the activities of antioxidant enzymes and the production of H 2 O 2 in rice (Shi et al 2012(Shi et al , 2014. In maize, ZmCCaMK was identifi ed to be essential for ABAinduced antioxidant defense ( Ma et al 2012a ). However, still there are not many reports on the role of CCaMK in abiotic stress; hence, in this article, I shall restrict the discussion to CDPK and CBL-CIPK proteins for their involvement in abiotic stress.…”
Section: +mentioning
confidence: 99%
“…Unlike CBL genes, CIPK isoforms were found to be induced under heat ( AtCIPK1, AtCIPK11, AtCIPK15, and AtCIPK24 ), salinity ( AtCIPK6, AtCIPK7, AtCIPK9, AtCIPK11, and AtCIPK12 ), oxidative ( AtCIPK23 ) stress, and low-K + ( AtCIPK9 ) condition . For global expression analysis of CBL and CIPK gene family in rice under varied stress conditions (salt, cold, heat, drought, and low potassium), the rice 57 K microarray datasets from Jain et al ( 2007 ), Ma et al ( 2012a , b ), and Walia et al ( 2005 ) were used as reference. Among the 34 OsCIPK genes, they found that 94 % (32/34) of them were differentially regulated under either of the stress conditions.…”
Section: Global Transcriptome Of Cbl-cipk Gene Family Across Plant Spmentioning
confidence: 99%